MENARCHE DINI DAN GANGGUAN MENSTRUSI PADA WANITA TERHADAP KEJADIAN KANKER OVARIUM - LILI NURMALIZA; RHINA CHAIRANI LUBIS (LP2MTBM MAKARIOZ, 2023)
Ovarian cancer is a disease in women that can cause death, where almost half of the mortality rate for all cancer patients, one of the causes is ovarian cancer, where ovarian cancer does not have typical clinical symptoms so that ovarian cancer sufferers come for treatment already in an advanced stage. It is estimated that 70-80% of ovarian cancer is only discovered after it has spread widely or has metastasized far so that the results of treatment are not as expected at the Pirngadi General Hospital Medan, the incidence of ovarian cancer is increasing, this study aims to see the relationship between early menarche and menstrual disorders in women. This type of study used a case control design with a sample of 48 people, with consecutive sampling, data were analyzed by Chi-Square with a significance limit of 5%, the results of this study showed that there was a relationship between early menarche and menstrual disorders in women with the incidence of ovarian cancer. where early menarche with a P-value of 0.013 and menstrual disorders with a P-value of 0.001, the conclusion of this study is that there is a relationship between early menarche and menstrual disorders in women to the incidence of ovarian cancer, for that it always has to be aware of anyone who is at risk for experiencing ovarian cancer.